Communicative Activities to develop the speaking skills to students of eighth grade at escuela de educación básica Alfa y Omega, La Libertad, Santa Elena province, school year 2015-2016. - Faubla Alomoto, Evelyn Damaris (2015)
The objective of the present study consists of finding suitable strategies to develop the speaking skills while learning English as a foreign language through communicative activities in the classroom based on the Communicative Approach. Oral communication is of great importance in the process of learning English. In order to achieve the objective set in the present study, the interaction between the main participants will be presented: the students and the teacher. The Communicative Approach together with other updated methods for the teaching of English contributes to the students` development of the speaking skills, and not the traditional grammar methods centered on accuracy of structures; it helps students to communicate easily if the content is closely related to real life and to the students´ needs and interests, being the main problem detected in this investigation. The type of investigation is the descriptive one. Different theoretical, empirical and statistical methods of investigation such as analysis, synthesis, induction, deduction, hypothetical, interviews, surveys, pedagogical tests and scientific observation were used in the different stages of this work to determine the theoretical bases that support the development of speaking skills of eighth graders at ESCUELA DE EDUCACIÓN BÁSICA “ALFA Y OMEGA”, La Libertad, Santa Elena Province, academic year 2015-2016 in order to improve the learning of a foreign language at this level. The present research paper will also be useful to identify the existing difficulties regarding the development of the speaking skills and sub-skills in the foreign language and to confirm the effectiveness of the implementation of the communicative activities designed. The results obtained are the improvement of the speaking skills of eighth-grade students, who were the direct beneficiaries.